INTEGRASI SYARIAH DALAM PERATURAN DAERAH INDONESIA: DIALEKTIKA FILSAFAT HUKUM ISLAM PROFETIK DAN PARADIGMA THOMAS KUHN: Sharia Integration in Indonesian Regional Regulations: Dialectics of Prophetic Islamic Law Philosophy and Thomas Kuhn's Paradigm - Gress Selly (UIN Kiai Haji Achmad Siddiq Jember, 2023)
The existence of Sharia Regional Regulations in Indonesia still reaps endless polemics over the suspicion of discriminatory policies that leads to human rights violations. Many Sharia Regional Regulations issued are influenced with the end of the Orde Baru regime which strongly encouraged the existence of sharia formalization into statutory regulations in the Reformasi Era. In practice, there are two different views in addressing the existence of these regional regulations, first where those who support the regulations by arguing the importance of regulating morality in society. On the other hand, these views are considered to be inconsistent with the state constitution and have a potential to cause socio-political turmoil considering that Indonesia is not a religious country. In addition, legal novelty becomes a necessity, where Thomas Kuhn argues that science is dynamic not static, legal science always experiences a revolution for legal novelty, and the adoption of Islamic law into positive law is a novelty for law paradigm in Indonesia. Using a literature study, this paper discusses how the principles of sharia integration into Regional Regulations using an overview of Islamic legal philosophy and the prophetic law paradigm. The results of the analysis show that the formalization of sharia into state administration affairs is influenced by historical factors to build the country with Islam as its national principle, as well as the influence of other factors such as social, cultural and religious. In the perspective of Islamic Law Philosophy, the function of legislation must be directed by policymakers to formulate rules oriented toward justice, expediency, and propriety. On the other hand, a review of Prophetic Law provides a view that Sharia Regional Regulations should not only limited to formal regulations which less represent values such as humanization, liberation, and transcendence. Keywords: Prophetic Law, Sharia Regional Regulation, Islamic Law, Legal Novelty, Thomas Kuhn. Keberadaan perda berbasis syariah di Indonesia masih menuai polemik yang tidak berkesudahan akibat kekahawatiran adanya kebijakan yang diskriminatif dan mengarah kepada pelanggaran hak asasi manusia. Banyak perda syariah yang muncul tidak terlepas dari selesainya pengaruh rezim orde baru yang mendorong semangat formalisasi syariah ke dalam peraturan perundang-undangan begitu kuat di era reformasi. Secara praktikal terdapat dua pandangan yang berbeda dalam menyikapi eksistensi dari perda tersebut, dimana pihak yang mendukung berargumentasi akan pentingnya pengaturan moralitas di masyarakat, di sisi lain pandangan tersebut justru dianggap tidak selaras dengan konstitusi negara, dan berpotensi menimbulkan gejolak sosial-politik mengingat negara Indonesia bukanlah negara agama. Selain itu, kebaruan hukum menjadi sebuah keniscayaan, dimana Thomas Kuhn berpendapat bahwa ilmu adalah dinamis bukan statis, Ilmu hukum senantiasa mengalami sebuah revolusi untuk kebaruan hukum, dan adopsi hukum islam kedalam hukum positif merupakan kebaruan dalam paradigma hukum di Indonesia. Menggunakan studi literatur, tulisan ini akan membahas bagaimana prinsip integrasi syariah ke dalam Perda menggunakan tinjauan filsafat hukum Islam dan paradigma hukum profetik. Hasil analisis menunjukkan bahwa, Formalisasi syariah ke dalam urusan penyelenggaraan negara tidak terlepas dari faktor historis untuk membangun negara berdasarkan Islam sebagai dasar negara, serta adanya pengaruh faktor lain seperti sosial, budaya dan agama yang telah mengakar kuat. Dalam perspektif Filsafat Hukum Islam, fungsi legislasi harus diarahkan oleh pembuat kebijakan untuk merumuskan aturan yang berorientasi kepada keadilan, kemanfaatan, dan kepatutan. Di sisi lain, tinjauan hukum profetik memberikan pandangan supaya adanya perda syariah tidak hanya sebatas peraturan formal yang kurang merepresentasikan nilai-nilai seperti humanisasi, liberasi dan transendensi. Kata Kunci : Hukum Profetik, Perda Syariah, Hukum Islam, Kebaruan Hukum, Thomas Kuhn.